Analisis Faktor-Faktor Keputusan Pembelian Kopi Mendhut di Kecamatan Gubug - Rahmawati, Sofiana Tri; Rahmawati, Dr. Bayu Kurniawan S.kom.,M.M; Rahmawati, Ira Setiawati S.E.M.S.i (Universitas PGRI Semarang, 2025)
This study aims to determine and analyze the effect of product quality, pricing, promotion and service quality on purchasing decisions for Mendhut Coffee in Gubug District. The population in this study were Mendhut Coffee consumers with a sample of 96 respondents. The sampling technique used is probability sampling technique with proportional random sampling method. In collecting data, this study used a Likert scale with 5 assessment criteria for 40 questions. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the product quality variable has a significant negative effect on the purchase decision of Mendhut Coffee. The pricing variable has a significant positive effect on the purchase decision of Mendhut Coffee. Promotion variables have a significant positive effect on the purchase decision of Mendhut Coffee. The service quality variable has a significant positive effect on the purchase decision of Mendhut Coffee. The variables of product quality, pricing, promotion, and service quality influence the purchase decision of Mendhut Coffee.